G11 Lung function, transfusion, pulmonary capillary blood volume and sickle cell disease. (27th April 2016) - Lunt, A; McGhee, E; Robinson, P; Rees, D; Height, S; Greenough, A
Abstract : Aims: Sickle cell disease is the most common inherited disorder in African and Caribbean populations. Restrictive lung function abnormalities become increasingly common in older patients and indeed are characteristic of sickle chronic lung disease. Young children with SCD, however, frequently have obstructive lung function abnormalities. It is not clear whether the obstructive abnormalities are due to asthma or the elevated pulmonary capillary blood volume seen in SCD children because of their chronic anaemia. Such data are essential to determine the most effective preventative strategies. Hence, our aim was to investigate whether blood transfusion in SCD children acutely increased pulmonary capillary blood volume (PCBV) and this was associated with increased airways obstruction. Methods: Measurements of respiratory system resistance and spirometry were made before and after blood transfusion in 18 children, median age 14.2 (6.6–18.5) years. The respiratory system resistance was measured using impulse oscillometry and a frequency of 5 Hz (Rrs5) and was used to assess small airway function. Lung function results were expressed as the percent predicted for height. Pulmonary capillary blood volume was measured using the single breath-hold method for gas transfer for carbon monoxide (DLCO) and nitric oxide (DLNO). Pulmonary membrane diffusing capacity (DMCO) and pulmonary capillary blood volume (PCBV) were then determined using the Roughton-Forster model. Results: Post transfusion, the median Rrs5 increased from 127.4 to 141.3% predicted for height (p < 0.0001) and pulmonary capillary blood volume from 39.7 to 64.1 ml/m2 (p < 0.0001). Forced expiratory volume in one second (p = 0.0056) and vital capacity (p = 0.0008) decreased. The increase in Rrs5 correlated with the increase in PCBV (r = 0.50, p = 0.0493). Conclusion: Significant increases in pulmonary capillary blood volume and respiratory system resistance occurred immediately following blood transfusion in children with SCD. Furthermore, the increase in respiratory system resistance significantly correlated with the increase in pulmonary capillary blood volume. These results provide evidence of a potential interaction between the increased pulmonary capillary blood volume and pulmonary function abnormalities seen in SCD children.